1990
DOI: 10.1111/j.1574-6968.1990.tb03792.x
|View full text |Cite
|
Sign up to set email alerts
|

Extremely thermostable amylolytic enzyme from the archaebacterium Pyrococcus furiosus

Abstract: One of the most thermostable and thermoactive enzymes ever described has been characterized from a hyperthermophilic archaebacterium Pyrococcus furiosus. The enzyme system of this bacterium was capable of hydrolyzing starch forming a mixture of various oligosaccharides. Unlike the amylases from aerobic bacteria this enzyme does not require metal ions for activity or stability. The enzyme is catalytically active over a very broad temperature range, namely between 40°C and 140°C. The half life of this peculiar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…This prediction would be in keeping with the failure of extensive efforts to find living organisms growing optimally at temperatures above 110 mC, since our concept of life rests heavily on the functioning of enzymes. However, enzymes have been found that have significant half-lives at 130 mC [8,10], and there is growing evidence that the degradative reactions to which proteins are subject are slower or do not occur in conformationally intact proteins. In other words, the upper temperature limit for protein stability may after all be determined by the conformational integrity of the protein, although we must bear in mind that little work on conformational or degradative stability has taken place above 100 mC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This prediction would be in keeping with the failure of extensive efforts to find living organisms growing optimally at temperatures above 110 mC, since our concept of life rests heavily on the functioning of enzymes. However, enzymes have been found that have significant half-lives at 130 mC [8,10], and there is growing evidence that the degradative reactions to which proteins are subject are slower or do not occur in conformationally intact proteins. In other words, the upper temperature limit for protein stability may after all be determined by the conformational integrity of the protein, although we must bear in mind that little work on conformational or degradative stability has taken place above 100 mC.…”
Section: Resultsmentioning
confidence: 99%
“…Even though this work was carried out on small peptides, it is difficult to envisage proteins that are stable enough to withstand this temperature. The most stable proteins found so far have half-lives in excess of 10 min at 130 mC [8], and greater stabilities have been shown for very stable enzymes immobilized and in the presence of stabilizing agents [9,11], so that prospects exist for characterizing denaturation and degradation up to 140 mC or so. Such stable proteins could also be starting points for attempts to engineer higher stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…furiosus amylase activity has been measured over broad temperature (40 -140°C) with an optimum activity at close to 100°C No loss of activity was detected after 6 hours of incubation at 90°C and at 120°C and about 10% of the initial activity was measured after 6 hours (Koch et al, 1990),. This equated to a decimal reduction time at 120°C of 6 hours (D 120 = 6 h).…”
Section: Introductionmentioning
confidence: 99%
“…The candidate organism: Pyrococcus furiosus was of great interest for the development of a sterilisation TTI because of the reported heat stability of its amylases (Koch, et al, 1990). The archaeon was isolated by Fiala and Stetter (1986) from shallow thermal waters near Vulcano Island, Italy.…”
Section: Introductionmentioning
confidence: 99%